P-87 Acvr1b rs2854464 is associated with quantitative measures of strength/power in lithuanian athletes and controls. (18th November 2016) - Shone, Kate; Innes, Aidan; Kilikevicius, Audrius; Statkeviciene, Birute; Stasiulis, Arvydas; Mamkus, Gediminas; Malkova, Dalia; Bailey, Mark ES; Venckunas, Tomas; Moran, Colin N
Abstract : Genetic variation is known to account for a large portion of the variation in muscle mass and strength/power in humans. However, few polymorphisms have been conclusively linked with these phenotypes. The myostatin signalling pathway is a source of potential candidates due to its involvement in muscle growth. Variation in myostatin itself has been shown to relate to muscle mass in humans; however, myostatin variation is rare in humans. Other studies have related variation in ACVR1B, a component of the myostatin signalling pathway, to strength/power phenotypes or to athlete status. However, this work still needs replication in large well phenotyped cohorts containing elite athletes. This study aims to replicate previous studies on the relationship between variation in the ACVR1B (rs2854464) G/A polymorphism and strength/power related phenotypes in well phenotyped Lithuanian athletes and controls. Participants DNA samples were from the GELAK cohort. This is comprised of 407 Lithuanians: 84 endurance athletes (END), 126 sprint-strength-power (SSP) and 197 controls (CON). Phenotypes related to stature (height, body mass, BMI), strength (isokinetic peak torque in left and right legs at 30 degrees per second), power (Wingate) and speed (30 m sprint). Genotypes were determined using bespoke RFLPs. Genotype distributions were compared by Chi squared. Odds ratios are reported as mean (lower to upper 95% confidence limits). Associations were established using GLM-ANOVA in Minitab. All GLM analyses were corrected for athlete group and age in months. The control sample was in Hardy-Weinberg equilibrium. Allele frequencies were similar to those reported in 1000 Genomes database. ACVR1B rs2854464 genotype distributions differed between SSP v END (p = 0.015) groups only. AA homozygotes were 2.16 (1.22 to 3.81) times more likely to be END than SSP (p = 0.007). After correction for age and athlete group, ACVR1B rs2854464 variation associated with body mass (p = 0.042, V = 1.36%), BMI (p = 0.016, V = 1.76%) and Wingate total anaerobic work (p = 0.021, V = 1.72%) but not with height, isokinetic peak torque, Wingate peak power or 30 m sprint speed. In all significant relationships, AA homozygotes were significantly weaker than GA heterozygotes. Variation in ACVR1B rs2854464 differs between endurance and strength athletes. It also relates to body mass and quantitative measurements of muscle function. However, in contrast to previous work, carriers of the A-allele are less likely to be strength/power athletes and even after correction for age and athlete group, carriers of the A-allele are still likely to have lower body mass and have lower capacity for anaerobic work. References: Windelinckx, et al . (2011) Comprehensive fine mapping of chr12q12-14 and follow-up replication identify activin receptor 1B (ACVR1B) as a muscle strength gene. Eur J Hum Gen 19 :208–215. Voisin, et al . (2016) ACVR1B rs2854464 Is Associated with Sprint/Power Athletic Status in a Large Cohort of Europeans but Not Brazilians. PLoS One 11 (6):e0156316.